Saving white women: vulnerability and the immobilized body in Don't Breathe (2016) - Christensen, Kyle; Levina, Marina (Communication and critical/cultural studies, 2022)
The horror thriller Don't Breathe (2016) follows three robbers as they invade the home of a blind Navy SEAL veteran who violently battles against them. Among the robbers is Rocky, a white woman desperately seeking financial security. Don't Breathe depicts Rocky's body in various states of physical immobility, signifying her vulnerability. By only recognizing the vulnerabilities of poor white women's bodies, the film leaves unrecognized the vulnerabilities of others, especially poor bodies of color and disabled bodies. Furthermore, through Rocky, the film suggests that white women can benefit from the violent aid of white patriarchy precisely because their vulnerability/immobility receives recognition.